Equivalence of Protection for Foreign and Domestic Creditors in Debt Restructuring Based on Positive Indonesian Law - Anugrah, Dikha; Akhamddhian, Suwari; Mulyani, Sri; Nnawulezi, Uche (Batulis Civil Law Review, 2025)
Introduction: This article analyzes the legal implications of excluding foreign creditors in corporate debt restructuring in Indonesia. The study highlights the challenges faced by foreign creditors in securing their rights within the Indonesian legal framework, particularly in bankruptcy and Suspension of Debt Payment Obligation (PKPU) proceedings. The case of PT Visi Media Asia serves as a reference to illustrate these challenges and their legal consequences.Purposes of the Research: The purpose of this study is to examine the legal impact of excluding foreign creditors in debt restructuring processes and to compare their legal position with domestic creditors under Indonesian law. By identifying regulatory gaps and inconsistencies, this study aims to provide recommendations for improving creditor protection and ensuring equal treatment in debt resolution mechanisms.Methods of the Research: This research employs a normative legal methodology, utilizing a statutory, conceptual, and analytical approach. Legal materials are collected through document studies, including legislation, court rulings, and scholarly literature. The qualitative analysis is applied to interpret legal norms and evaluate their implementation in real cases, particularly focusing on the case of PT Visi Media Asia.Results Main Findings of the Research: The findings reveal that Indonesia's current legal framework does not fully safeguard foreign creditors in debt restructuring, often favoring domestic creditors in judicial and regulatory practices. The study contributes to the discourse on legal reform by recommending clearer regulations and stricter enforcement to ensure fairness in debt restructuring, fostering investor confidence in Indonesia’s financial system.